P5_11 Can Volcanoes Make Venus Habitable? - Cox, Tom; Penn Fernandez, Keaton; Mead, Lara; Seagrave, Joshua (Physics Special Topics, 2020)
This paper dives into the uses of converting Carbon dioxide (CO2) into Oxygen (O2). The aim of this paper is to examine if Venus’ atmosphere could be terraformed to allow humans to breathe on the surface of the planet. What was found was that using power generated from 37 volcanoes known to be on Venus, it would take 186,666 MOXIE machines 1.38 × 1015 hours to convert Venus’ atmosphere to 20% O2